Adulticidal activity of star anise, turmeric, cloves and combinations against houseflies - Sinthusiri, J.; Soonwera, M.; Puwanard, C.; Passara, H.; Thongsaiklaing, T.; Moungthipmalai, T.; Sittichok, S.; Jintanasirinurak, S. (International Journal of Agricultural Technology, 2025)
The small droplet size could increase the absorbed ingredients and high stability. The star anise nanoemulsion was determined optimum efficacy, with a 1% concentration resulting in the highest knockdown and mortality rate of 100%. Its KT50 and mortality effective values were 28 min and 36 times, respectively. Furthermore, the adult stage of houseflies is found to be susceptible to star anise nanoemulsion. In contrast, cypermethrin was less toxic to it, with a high KT50 and resistance to adult houseflies. Consequently, the star anise nanoemulsion could be developed into an efficient and safe environment for controlling housefly populations.